Vascular Access Device Infections: Current Management Practices and the Role of Multidisciplinary Teams at a Large Hospital in Northern Italy - Marta Colaneri; Lucia Galli; Martina Offer; Fabio Borgonovo; Giovanni Scaglione; Camilla Genovese; Rebecca Fattore; Monica Schiavini; Giovanni De Capitani; Maria Calloni; Arianna Bartoli; Antonio Gidaro; et al. (Antibiotics)
Introduction: Vascular access device (VAD)-associated infections, including catheter-related (CRBSI) and catheter-associated bloodstream infections (CABSI), present significant challenges in patient care. While multidisciplinary VAD teams (VATs) are equipped with protocols for managing these infections, adherence to these guidelines in real-life practice is inconsistent. This study aims to evaluate the alignment between actual VAD infection management practices and VAT-recommended protocols. Methods: We conducted a retrospective, single-center study at Luigi Sacco Hospital (May 2021–October 2023) involving non-ICU adult patients with diagnosed CRBSI or CABSI. VAT experts independently reviewed infection management choices, which were divided into eight specific procedural options. These options included variations in VAD removal, timing of repositioning, and combinations of antimicrobial lock therapy and systemic therapy. Concordance between real-life practices and VAT recommendations was evaluated using Cohen’s kappa coefficient. Results: Of 2419 VAD placements, 146 (6%) developed infections (84 CABSI, 62 CRBSI). Clinicians removed VADs in 66.4% of cases compared to 62.3% per VAT recommendations, with moderate overall agreement (Cohen’s kappa = 0.58). Analysis of the eight management categories revealed moderate to low alignment (unweighted kappa = 0.44, weighted kappa = 0.30) between real-life practices and VAT guidance, with slightly improved concordance in CRBSI cases. Conclusions: Our findings underscore a discrepancy between real-life VAD infection management and VAT-recommended protocols, suggesting a need for clearer, more accessible guidelines and increased multidisciplinary collaboration. Enhanced VAT consultation and simplified protocol dissemination may improve consistency in infection management and ultimately lead to better patient outcomes.